Dendrobium officinale leaves as a new antioxidant source. (October 2017) - Zhang, Yuan; Zhang, Lihong; Liu, Jingjing; Liang, Junling; Si, Jinping; Wu, Shihua
Graphical abstract: Highlights: Leaves of D. officinale were found to have potent antioxidant activities. 14 flavonoids were distinguished as herb-marker peaks by HPLC-DAD-based pattern recognition technologies. Its antioxidant principles were determined by DPPH/ABTS + -HPLC antioxidant assays. Rutin was found to be a major antioxidant principle of the leaves of D. officinale. Therefore, leaves of D. officinale may be new antioxidant sources. Abstract: In this work, we found that the extract of leaves of a famous Traditional Chinese Medicine TiepiShihu ( Dendrobium officinale Kimura et Migo) contained high content of flavonoids ranging from 7.66 mg·g − 1 to 9.50 mg·g − 1 dried weight and possed potent antioxidant activities. There was a strong positive correlation between DPPH radical scavenging rate and total flavonoids content. Furthermore, the antioxidant principles were determined by combination use of DPPH/ABTS + -HPLC assays and HPLC-DAD-based pattern recognition technologies. Their structure was further identified by on-line and off-line HPLC-ESI-MS/MS and following targeted isolation and NMR recognition. 14 phenolic herber-markers including quercetin-type flavonols and apigenin-type flavones were characterized from the leaves of D. officinale . The major flavonoid component of leaves was rutin and its content ranged from 1.33 to 2.89 mg·g − 1 dry weight. In summary, whole results indicated that the leaves of D. officinale might be developed as antioxidant sources for medicinal and health food resources.